ANALYSIS OF THE FINANCING OF PROJECTS IN THE ENERGY SECTOR - Fayziyev, Samandar (Sanoatda raqamli texnologiyalar, 2023)
As can be seen from the article which discusses the state of financing projects in the energy sector and the problems observed in it, the development processes of the energy sector, the status of thermal, wind and solar power plants in our country and their difference from each other in terms of their effectiveness, as well as alternative financing directions. The purpose of the study is to analyze the financing and sustainability of infrastructure projects in the energy sector.